2017
DOI: 10.1021/acs.macromol.6b02151
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Fluorinated Phenanthrene Monomers Using Mallory Reaction and Their Copolymerization

Abstract: The Mallory reaction of 1,2-diarylhexa­fluoro­cyclopentene (1, aryl = 3-bromophenyl; 2, aryl = 4-bromophenyl) under light irradiation (λ = 365 nm) in the presence of iodide proceeded to give dibromo­phenanthrene derivatives, 3 and 4. Polycondensation of 9,9-dioctylfluorene-2,7-diboronic acid bis­(1,3-propanediol)­ester with the obtained monomers by Suzuki–Miyaura coupling afforded the phenanthrene-type copolymers Poly-3 and Poly-4 in high yields. For comparison, diphenylethene-type copolymers (Poly-1 and Poly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In our initial report dedicated to the synthesis and properties of the first tetrathiafulvalene-helicene (TTF-Hel) derivatives as precursors for chiral electroactive materials, [14,24] we have described the oxidative photocyclization of 1 a as providing exclusively the 2,3-dibromo- [4]helicene 2 a (Scheme 4), [23] in agreement with similar regioselectivity observed for other meta-substituted bromo-stilbenes. [16][17][18] The dibromo-helicene 2 a was subsequently used in a bis-Stille coupling reaction to provide a protected helicene-bis(thiolate). However, a closer inspection now of the reaction products of the Mallory reaction on 1 a reveals that, besides 2 a, the monobromo derivative 4 a is also formed in a ratio 2 a:4 a of ~2:1 (Scheme 4).…”
Section: Reactivity Of Dihalostyryl-naphthalenes In Oxidative Photocy...mentioning
confidence: 99%
See 1 more Smart Citation
“…In our initial report dedicated to the synthesis and properties of the first tetrathiafulvalene-helicene (TTF-Hel) derivatives as precursors for chiral electroactive materials, [14,24] we have described the oxidative photocyclization of 1 a as providing exclusively the 2,3-dibromo- [4]helicene 2 a (Scheme 4), [23] in agreement with similar regioselectivity observed for other meta-substituted bromo-stilbenes. [16][17][18] The dibromo-helicene 2 a was subsequently used in a bis-Stille coupling reaction to provide a protected helicene-bis(thiolate). However, a closer inspection now of the reaction products of the Mallory reaction on 1 a reveals that, besides 2 a, the monobromo derivative 4 a is also formed in a ratio 2 a:4 a of ~2:1 (Scheme 4).…”
Section: Reactivity Of Dihalostyryl-naphthalenes In Oxidative Photocy...mentioning
confidence: 99%
“…[15] Intriguingly, the case of the bromine substituent in the meta position in a series of stilbenes has been only mentioned in a few reports describing the preparation of the corresponding phenanthrenes with the Br substituent in position 2, without any evidence for the formation of the other possible isomer with Br in position 4, which is one of the two inner positions in phenanthrenes. [16][17][18] The authors thus concluded that the ring closure reaction was highly regioselective, in spite of the yields observed for the various 2-Br-phenanthrenes reaching up to a maximum of 50 %. When the Br substituent is located in the para position, no regioselectivity issues occur.…”
Section: Introductionmentioning
confidence: 99%
“…[36] With these considerations in mind, we designed and synthesized several X-shaped phenanthrene derivatives that contain the same or different aryl substituents (π 1 and π 2 , Figure 1) at the 1,8-and 3,6-positions. The synthetic routes for preparation of these substances utilized photo-dehydrogenation cyclization reactions [37][38][39][40][41] of stilbenes containing two bromine and two chlorine groups. Suzuki coupling reactions of the poly-halogen substituted phenanthrenes, 1 and 2, produced in this manner generated the target phenanthrenes 3 a-c possessing four 4-tert-butylphenyl (t-Buph), 9,9-dimethyl-9Hfluoren-2-yl (DMFlu) or 4-diphenylaminophenyl (DPAP) groups (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported the syntheses of PAHs fused with HFCP, i.e., HFCP‐PAHs . Schemeà displays the synthetic route to these compounds.…”
Section: Introductionmentioning
confidence: 99%